CRYSTALLINS IN RETINAL GANGLION CELL SURVIVAL AND REGENERATION - Piri, Natik (2013)
Crystallins are heterogeneous proteins classified into alpha, beta, and gamma families. Although crystallins were first identified as the major structural components of the ocular lens with a principal function to maintain lens transparency, further studies have demonstrated the expression of these proteins in a wide variety of tissues and cell types. Alpha crystallins (alpha A and alpha B) share significant homology with small heat shock proteins and have chaperone-like properties, including the ability to bind and prevent the precipitation of denatured proteins and to increase cellular resistance to stress-induced apoptosis. Stress-induced upregulation of crystallin expression is a commonly observed phenomenon and viewed as a cellular response mechanism against environmental and metabolic insults. However, several studies reported downregulation of crystallin gene expression in various models of glaucomatous nerodegeneration suggesting that that the decreased levels of crystallins may affect the survival properties of retinal ganglion cells and thus, be associated with their degeneration. This hypothesis was corroborated by increased survival of axotomized retinal ganglion cells (RGCs) in retinas overexpressing alpha A or alpha B crystallins. In addition to RGC protective functions of alpha crystallins, beta or gamma crystallins were implicated in RGC axonal regeneration. These findings demonstrate the importance of crystallin genes in RGC survival and regeneration and further in-depth studies are necessary to better understand the mechanisms underlying the functions of these proteins in healthy RGCs as well as during glaucomatous neurodegeneration, which in turn could help in designing new therapeutic strategies to preserve or regenerate these cells.